Storing electricity as chemical energy : beyond traditional electrochemistry and double-layer compression - Antonietti, Markus (2020)
Extending the range of analysis of previous measurements on energy storage in ionic liquid (IL)-based supercapacitors with very well defined carbon materials indicates that there are two distinct processes at play: the one at lower voltages is (classically) related to the micropore inclusion of single ions, while a previously unknown high voltage transition can be ascribed to a change in the structure and coordination number of the ionic liquid. This opinion article discusses a proof of circumstantial evidence for this so far weakly understood and often overlooked mode of energy storage, which in principle could take supercapacitors to a new level of energy storage.